Open surgery for carpal tunnel syndrome: is it necessary to release the antebrachial fascia? A randomized clinical trial study - Razavipour, Mehran; Taheri, Sadegh; Abdollahi, Amirsaleh; Yahaghi, Yazdan (Frontiers in Surgery, 2024)
BackgroundOpen surgery for carpal tunnel syndrome (CTS) has historically involved release of the antebrachial fascia. The benefit of antebrachial fascia release in CTS surgery is still controversial. So, this study was designed to evaluate this hypothesis.MethodsThe study was designed as a two-arm randomized clinical trial study. Patients diagnosed with bilateral carpal tunnel syndrome were enrolled in the study, while those under 18 years of age and those with a history of carpal tunnel release, trauma to the spine, shoulder, or elbow, rheumatologic disease, inflammatory arthropathy, and CTS onset during pregnancy were excluded. The hands of the eligible patients were randomly assigned to two surgical groups. In the first group, the antebrachial fascia was opened to the proximal part, while in the second group, the fascia was opened from the central part of the deep layer to the distal volar part of the wrist. Pain severity, grip and pinch strength, symptom severity, and functional status were evaluated by the visual analog scale, the SAEHAN® hydraulic handgrip and pinch dynamometer, and the Boston Carpal Tunnel Questionnaire (BCTQ), respectively, at the baseline and 1, 3, and 6 months after surgery.ResultsFinally, 230 patients (220 women and 10 men, 460 hands) completed the study. The mean age of the patients was 50.4 ± 8.4 years. In both open surgery groups with and without antebrachial fascia release, the grip and pinch strength, BCTQ scores, and pain severity significantly improved at the end of the study (P < 0.01), but there was no statistically significant difference between the two groups (P > 0.05). Patient satisfaction improved in both groups; again, no significant difference was observed between the two groups (P > 0.05).ConclusionBoth open CTS surgery with and without antebrachial fascia release show the same clinical and functional outcomes. Therefore, avoiding the release of the antebrachial fascia preserves proprioception and prevents iatrogenic injury to the median nerve and its branches. Conversely, a blunt release of the antebrachial fascia does not adversely affect the outcome. Clinical Trial Registrationhttps://irct.behdasht.gov.ir/search/result?query=@irct_id:IRCT2012103111341N1, Identifier: IRCTID: IRCT2012103111341N1.